1997
DOI: 10.1002/jor.1100150222
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of bone formation by intraosseous application of recombinant basic fibroblast growth factor in normal and ovariectomized rabbits

Abstract: The effect on intraosseous bone formation of a single local injection of recombinant human basic fibroblast growth factor into the distal femur was examined in normal and ovariectomized rabbits. In normal rabbits, basic fibroblast growth factor increased bone mineral density around the injected site in a dose-dependent manner at 4 weeks, with significant effects at concentrations of 400 micrograms and greater. Doses of 400 and 1,600 micrograms of basic fibroblast growth factor increased bone mineral density by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 28 publications
6
54
0
Order By: Relevance
“…Based on the evidence of extensive studies using various animal models, [6][7][8][9][10][11][12][13][14][15] this study for the first time showed clinical evidence that rhFGF-2 in gelatin hydrogel accelerated radiographic bone union of the closing wedge high tibial osteotomy. Because most osteotomies can heal only with appropriate fixations, and in fact, all patients even of the low dosage group eventually achieved radiographic bone union in the present study, the rhFGF-2 application may not have yielded bone union by preventing nonunion, but just accelerated bone union.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on the evidence of extensive studies using various animal models, [6][7][8][9][10][11][12][13][14][15] this study for the first time showed clinical evidence that rhFGF-2 in gelatin hydrogel accelerated radiographic bone union of the closing wedge high tibial osteotomy. Because most osteotomies can heal only with appropriate fixations, and in fact, all patients even of the low dosage group eventually achieved radiographic bone union in the present study, the rhFGF-2 application may not have yielded bone union by preventing nonunion, but just accelerated bone union.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, previous animal studies demonstrated that a single injection of FGF-2 enhanced the proliferation of chondroprogenitor cells in fracture callus, causing the formation of a larger cartilage, but did not directly affect maturation of chondrocytes or replacement of the cartilage by osseous tissue. 7,14,23 Furthermore, expressions of FGF-2, FGF-1, and their principal receptor FGFR1 have been identified mainly at the early stage of fracture healing. 1,[24][25][26] In addition to its mitogenic action on immature mesenchymal cells, FGF-2 may induce other anabolic factors such as prostaglandins, transforming growth factor (TGF)-b and bone morphogenetic proteins (BMPs), which may compose a serial cascade of bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone tissues, FGF-2 is produced by cells of osteoblastic lineage, is accumulated in bone matrix, and acts as an autocrine/paracrine factor for bone cells (6 -10). We and others have reported that the exogenous application of FGF-2 has stimulatory effects on bone formation in several in vivo models as a pharmacological action of FGF-2 (11)(12)(13)(14)(15)(16)(17). On the other hand, in vitro studies revealed that high concentrations of FGF-2 (10 Ϫ9 -10 Ϫ8 M) stimulated osteoclastogenesis in bone marrow culture (18) and bone resorption in bone organ cultures (19,20).…”
Section: Fgf-2 (>10mentioning
confidence: 99%
“…Recent reports have shown that the addition of exogenous FGF-2 to a fracture site or bone defect during the early healing stage accelerates fracture repair and bone formation 8 . However, no experimental studies have been performed to investigate the expression of FGF-2 during bone regeneration.…”
Section: Introductionmentioning
confidence: 99%